Local SDF-1α application enhances the therapeutic efficacy of BMSCs transplantation in osteoporotic bone healing - Qian Liu; Yi Wen; Jun Qiu; Zhaoyichun Zhang; Zuolin Jin; Meng Cao; Yang Jiao; Hongxu Yang (Heliyon, 2020)
Bone defect healing is markedly impaired in osteoporotic patient due to poor bone regeneration ability. Stromal cell derived factor-1α (SDF-1α) plays a pivotal role in the repair of various injured tissues including bone. Here, we definite that SDF-1α hydrogels potentiates in vivo osteogenesis of bone marrow-derived stromal stem cells (BMSCs) in osteoporosis. The characteristics of rat primary BMSCs including superficial markers by flow cytometry and multi-lineage differentiation by induction were determined. At different time intervals, the release media from the SDF-1α-releasing hydrogels were collected to identificate SDF-1α exhibited a sustained release profile and maintained its bioactivity after release from the hydrogels to stimulate chemotaxis of BMSCs in a time dependent manner. Bilateral alveolar defects were operated in ovariectomized (OVX) rats and repaired with systemic BMSCs transplantation with or without the hydrogels. Local administration of SDF-1α significantly enhanced BMSCs recruitment and promoted more bone regeneration as well as the expression of OCN and Runx2 compared with the effect of BMSCs transplantation alone. Moreover, after BMSCs transplantation with SDF-1α delivery, macrophage polarization was promoted toward the M2 phenotype, that is identified as an important symbol in tissue regeneration process. Taken together, local SDF-1α application enhances the efficacy of BMSCs transplantation therapy in osteoporotic bone healing, suggesting clinical potential of SDF-1α to serve as a therapeutic drug target for osteoporosis treatment.